2019
DOI: 10.1002/ijc.32363
|View full text |Cite
|
Sign up to set email alerts
|

NK‐ and T‐cell subsets in malignant mesothelioma patients: Baseline pattern and changes in the context of anti‐CTLA‐4 therapy

Abstract: Malignant mesothelioma (MM) is a highly aggressive form of cancer with limited treatment options. Although the role of NK cells has been studied in many solid tumors, the pattern of NK‐cell subsets and their recognition of mesothelioma cells remain to be explored. We used RNA expression data of MM biopsies derived from the cancer genome atlas to evaluate the immune cell infiltrates. We characterized the phenotype of circulating NK and T cells of 27 MM patients before and after treatment with an anti‐CTLA‐4 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 48 publications
(85 reference statements)
1
30
0
Order By: Relevance
“…In general, assays that require a biopsy are less suitable in multimetastatic patients because some lesions might not be accessible. Blood tests may overcome this limitation, as reported by Sottile et al They demonstrated that before anti-CTLA4 therapy, patients affected by malignant mesothelioma showed reduced frequencies of CD56dim and increased frequencies of CD56bright NK cells [90]. After therapy, the ratio reverted back to normal physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In general, assays that require a biopsy are less suitable in multimetastatic patients because some lesions might not be accessible. Blood tests may overcome this limitation, as reported by Sottile et al They demonstrated that before anti-CTLA4 therapy, patients affected by malignant mesothelioma showed reduced frequencies of CD56dim and increased frequencies of CD56bright NK cells [90]. After therapy, the ratio reverted back to normal physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, higher levels of intratumoral NK cells have been correlated with response to anti-CTLA-4 [89,90]. Moreover, in patients with malignant mesothelioma, a perturbation of the PB CD56bright/dim ratio was observed compared to healthy donors, which normalized in favor of the CD56 dim effector NK cells after treatment with tremelimumab, an IgG2 anti-CTLA-4 mAb [91]. Interestingly, in patients with melanoma, lower levels of CD56 dim NK cells were also found, which increased after treatment with ipilimumab, the first approved anti-CTLA-4 mAb [92].…”
Section: Ctla-4mentioning
confidence: 99%
“…However, there were still many patients who are nonresponsive to these treatments. However, recent findings indicate that improved survival highly correlates with the frequency of DNAM-1 + CD56 dim NK and NKp46 + CD56 dim NK cells after treatment with anti-CTLA-4 in patients with malignant mesothelioma (125). Hsu and Hodgins et al demonstrated in multiple tumor models that PD-1 is upregulated on the most activated and functionally responsive intratumoral NK cells, suggesting that the efficacy of PD-1 blockade depends in part on inducing an NK cell-based antitumor response (126).…”
Section: Perspectivementioning
confidence: 99%